Superparamagnetic Luminescent MOF@Fe3O4/SiO2 Composite Particles for Signal Augmentation by Magnetic Harvesting as Potential Water Detectors - Wehner, Tobias; Mandel, Karl; Schneider, Michael; Sextl, Gerhard; Mueller-Buschbaum, Klaus (ACS Applied Materials and Interfaces, 2016)
Herein, we present the generation of a novel complex particle system consisting of superparamagnetic Fe3O4/SiO2 composite microparticle cores, coated with luminescent metal-organic frameworks (MOFs) of the constitution 2 ∞[Ln2Cl6(bipy)3]·2bipy (bipy = 4,4′-bipyridine) that was achieved by intriguing reaction conditions including mechanochemistry. The novel composites combine the properties of both constituents: superparamagnetism and luminescence. The magnetic properties can be exploited to magnetically collect the particles from dispersions in fluids and, by gathering them at one spot, to augment the luminescence originating from the MOF modification on the particles. The luminescence can be influenced by chemical compounds, e.g., by quenching observed for low concentrations of water. Thus, the new composite systems present an innovative concept of property combination that can be potentially used for the detection of water traces in organic solvents as a magnetically augmentable, luminescent water detector.
CRIS-Team Scopus Importer:2020-04-02
Keywords: composites; luminescence; magnetic particle detectors; metal organic frameworks (MOFs); superparamagnetism; water detectors